The effect of egg embryonation on field-use of a hookworm benzimidazole-sensitivity egg hatch assay in Yunnan Province, People's Republic of China. - Andrew C Kotze; Peter Steinmann; Hui Zhou; Zun-Wei Du; Xiao-Nong Zhou (Public Library of Science (PLoS), 2011)
BACKGROUND: Current efforts to control human soil-transmitted helminths (STHs) involve the periodic mass administration of benzimidazole drugs to school aged children and other at- risk groups. Given that high levels of resistance to these drugs have developed in roundworms of livestock, there is a need to monitor drug efficacy in human STHs. The current study aimed to evaluate an in vitro egg hatch assay for measuring the sensitivity of human hookworms to benzimidazole drugs in an isolated field setting in southern Yunnan province, People's Republic of China. METHODOLOGY/PRINCIPAL FINDINGS: Egg hatch assays were performed with hookworm (Necator americanus) eggs extracted from 37 stool samples received from local school-aged children. The mean IC(50) was 0.10 ug/ml thiabendazole (95% CIs: 0.09-0.12 ug/ml). Observation of the eggs immediately prior to assay set-up revealed that a small percentage had embryonated in some samples. Scoring of % embryonation of eggs prior to the assay allowed for corrections to be made to IC(50), IC(95) and IC(99) values. Examination of the data with and without this correction revealed that the embryonation of a small number of eggs did not affect IC(50) values, but did increase IC(95) and IC(99) values for some samples. CONCLUSIONS/SIGNIFICANCE: This study has highlighted the impact of egg embryonation on the use of benzimidazole drug sensitivity assays for human hookworms in field settings. Given the greater flexibility required in human stool collection procedures compared to livestock studies, we suggest that embryonation of some eggs may be an unavoidable issue in some human studies. Hence, it needs to be measured and accounted for when analysing dose response data, particularly for generation of IC(95) and IC(99) values. The protocols used in this study and our suggested measures for accounting for egg embryonation should have widespread application in monitoring benzimidazole sensitivity at field sites worldwide.